Addressing Unpaid Work in Cambodia - You, Sotheary (HAPSc Policy Briefs Series, 2020)
This paper presents an overview of development challenges related to promoting gender equality in Cambodia based on the available published evidence. To achieve gender equality objectives, Cambodia needs policy initiatives that address unpaid work and facilitate women's equal participation in labor and social development. This paper offers policy recommendations to address Cambodia's unpaid work issues, including the provisions of elderly care, enhancement of early childhood education coverage, promoting accessible and affordable childcare programs, pushing for parental leave, and increasing pension scheme coverage. The success of policy design and implementation requires political will to deliver the policies, accompanying efficient and effective public service delivery.